A brief review on the phytochemistry and pharmacological activities of Morinda citrifolia L. - Ibrahim, Siti Norsyafiqah; Haron, Norhisham; Abdullah, Anas; Rahmat Sam, Mohd Fuad (UPM, 2024)
Morinda citrifolia L., commonly known as mengkudu in Malaysia, is a medicinal plant utilized for thousands of years to treat various health problems. The plant has been widely used in traditional medicine, especially among the Malay community. However, there is little scientific proof of the medicinal properties of the plant. Thus, this review discussed and summarized the latest scientific findings on the phytochemistry and pharmacological activities of M. citrifolia L. The research articles were gathered from various electronic databases and following the title, abstract and content screening, a total of 136 articles were selected from SCOPUS (56), Web of Science (25), Science Direct (16), and Google Scholar (39) from 2016 to 2022. The duplicated articles from the databases were then eliminated. Information was gathered from the resulting 45 articles and discussed in this review. The data suggested that phytochemical compounds, mainly from the phenolics and flavonoids classes, found within different parts of the M. citrifolia L. plant possessed biological activities, including antibacterial, antioxidant, anti-diabetic, anti-obesity, anticancer, and antihypertensive properties. Factors such as the conditions and solvents used during the extraction process played essential roles in investigating the therapeutic properties of different parts of the plant. Although M. citrifolia L. could treat diseases, more clinical trials are needed to understand its therapeutic and preventive effects. Malaysian Journal of Medicine and Health Sciences (2024) 20(3): 339-348. doi:10.47836/mjmhs.20.3.45